Biosensor Technology: Advances and Applications in Livestock Infectious Disease Diagnosis - Yanan Zhao; Lu Zhang; Aihua Wang; Dong Zhou (Veterinary Sciences)
Biosensors have revolutionized the diagnosis of infectious diseases in livestock by offering sensitive and rapid detection methods for important pathogens. These devices, particularly luciferase-based biosensors, convert biological responses into quantifiable signals, enabling the real-time, non-invasive monitoring of critical biomarkers. This review explores the development and advantages of biosensors, focusing on their applications in detecting important livestock pathogens, including bacteria, parasites, and viruses. By comparing biosensors with traditional diagnostic methods, the review highlights their superior sensitivity and specificity in diagnosing obstetric infections. Furthermore, it discusses the broader utility of biosensors in monitoring gene expression, protein localization, and cellular events. Together, biosensors provide new tools for the timely diagnosis of infectious diseases in livestock and are critical to improving livestock health.